Наблюдение параметрического рентгеновского излучения от протонов с энергией 50 ГэВ; Известия вузов. Физика; Т. 56, № 11-2 - Афонин А. Г. Александр Гаврилович; Бритвич Г. И. Геннадий Иванович; Чесноков Ю. А. Юрий Андреевич; Дурум А. А. Артур Андреевич; Костин М. Ю. Михаил Юрьевич; Лутчев А. В. Александр Вениаминович; Маишеев В. А. Владимир Александрович; Янович А. А. Андрей Антонович; Щагин А. В. Александр Васильевич; Трутень В. И. Валентин Иванович; Ганенко В. Б. Владимир Борисович; Кириллин И. В. Игорь Владимирович; et al. (2013, 2013)
Заглавие с экрана